Therapeutically targeting essential metabolites to improve immunometabolism manipulation after liver transplantation for hepatocellular carcinoma - Zhang, Wenhui; Zhao, Yu; He, Qiang; Lang, Ren (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver malignancy globally and is associated with a poor prognosis. Sophisticated molecular mechanisms and biological characteristics must be explored to gain a better understanding of HCC.The role of metabolites in cancer immunometabolism has been extensively recognized as a hallmark of cancer in the tumor microenvironment (TME). Recent studies have focused on metabolites derived from carbohydrate, lipid, and protein metabolism, as alterations in these may contribute to HCC progression, ischemia-reperfusion (IR) injury during liver transplantation (LT), and post-LT rejection. Immune cells play a central role in the HCC microenvironment and in the duration of IR or rejection by shaping immune responses through metabolite modifications, engaging in complicated crosstalk with tumor cells. A growing number of publications suggest that the functions of immune cells in the TME are closely related to metabolic shifts. In this review, we summarize recent findings on the primary metabolites in TME and post-LT metabolism, and relate these studies to HCC development, IR injury, and post-LT rejection. Our understanding of aberrant metabolism and targeting metabolites based on regulatory metabolic pathways may provide a novel strategy to enhance immunometabolism manipulation by reprogramming cell metabolism.